Studi Komparasi Strategi Pembelajaran Mind MappingDengan Index Card Match Terhadap Hasil BelajarIPA Siswa Kelas IV SDIT Nur Hidayah SurakartaTahun Pelajaran 2015/2016 - FATMAWATI, ANISA; , Drs. Suwarno, SH., M. Pd (2016)
ABSTRACT Anisa Fatmawati/A510120203. COMPARISON STUDY BETWEEN STRATEGY OF MIND MAPPING WITH INDEX CARD MATCH IN LEARNING OUTCOME OF NATURAL SCIENCE AT THE 4th GRADE STUDENTS OF SDIT NUR HIDAYAH 2015/2016 ACADEMIC YEAR. Research Paper: School Of Teacher Training and Education, Muhammadiyah University of Surakarta. March, 2016. This research is aiming at (1) differences in the use of mind mapping's strategy with index card match's strategy auctioned in learning outcome of natural science at the 4th grade students of SDIT Nur Hidayah Surakarta 2015/2016 academic year, (2) a better implementation in learning outcome of natural science between mind maping's strategy with index card match's strategy at the 4th grade students of SDIT Nur Hidayah Surakarta 2015/2016 academic year. This research is experiment quantitative. The Subject of this research is all students at 4th grade of SDIT Nur Hidayah Surakarta 2015/2016 academic year. The tehnique of collecting data is test and documentation. Test instruments include test the validity and reliability testing. The tehnique of analizing data is t-test which doing pre-requisite test like homegenity test and normality test first. Based on the data analysis about 5% degree's significance the result shows ttest > ttable is 2,0722 > 1,993 which the average of the learning outcome at 4th grade C is higher than the learning outcome at 4th grade D, is 85,1 > 82,5. The conclusion is (1)there are differences in leraning outcome of natural science using mind mapping's strategy and index card match's strategy auctioned in learning outcome of natural science at the 4th grade students of SDIT Nur Hidayah Surakarta 2015/2016 academic year. (2) mind mapping's strategy is bigger than index card match's strategy auctioned in learning outcome of natural science at the 4th grade students of SDIT Nur Hidayah Surakarta 2015/2016 academic year. Keyword: index card match strategy, learning outcome, mind mapping strategy.